Research on Precision Marketing Strategy Based on Cluster Analysis Algorithm - Wang, Haoran; Wang, Junsheng; Zhong, Ziqi (2020 International Conference on E-Commerce and Internet Technology (ECIT), 2020)
Entering the 21st century, the advancement of technology and the rapid pace of life of people will generate huge amounts of data every day, which promotes the development of big data. The rise of big data and the development of data mining technology have led to the rapid development of precision marketing theory. Relying on multi-platform data collection and big data technology analysis and prediction capabilities, it can accurately focus on target markets and customers, making corporate advertising more accurate and effective, and bringing higher return on investment for enterprises. Based on modern marketing concepts, this article introduces the concepts and characteristics of precision marketing and customer segmentation theory. Since precision marketing is based on cluster analysis algorithm, then, this article introduces the cluster analysis algorithm, focusing on the K-means algorithm in cluster analysis. Then, in conjunction with the theory of precision marketing, this paper presents the process of data mining. Based on this, the strategy of precision marketing is given.